WATER QUALITY OF AL-HAMMAR MARSH SOUTH IRAQ (Journal of Engineering, 2009)
Water quality plays an important role in the restoration of marshes south Iraq, hence, in this paper water samples were taken from different sites in Hammar marsh in south of Iraq to know the variation of some water parameters with the distance along Hammar marsh. The water samples will submit to chemical and physical analyses.Ten water samples were analysis to discuss the results of these parameters and give reasons for changing these parameters with the location along the Hammar marsh. It was found that the concentrations of Biochemical Oxygen Demand (BOD) and Dissolved Oxygen (DO) with the acceptable range for drinking and agriculture uses, DO concentrations did not decreased less than 6 mg/l.The analyses showed that high concentrations of The Total Dissolved Solids (TDS) and Electrical Conductivity (EC) at the beginning and end of the marsh, the analyses showed a decrease in these parameters at the middle of the marsh.The analyses showed low concentrations of Total Suspended Solids (TSS) along the Al-Hammar marsh, the concentration of TSS strongly depends on the velocity of water in marsh which is considered low at the study region. As well as the analyses showed that the Mg concentration increased above 125 mg/l level, this level may cause diarrhea.It was also found that the concentrations of sulphates exceed allowable limits of WHO standards for drinking water (400 mg/l), these concentrations of SO4 came from severally burned of organic matter in soils after drainage period.